2019
DOI: 10.1177/1179550619845331
|View full text |Cite
|
Sign up to set email alerts
|

Taste Function in Healthy Taiwanese Adults

Abstract: Objective: In this work, our aim was to measure the taste function of healthy Taiwanese adults using 2 commonly used taste tests. Methods: The taste function of 102 healthy Taiwanese adults was evaluated using the whole-mouth suprathreshold taste test and the taste quad test. In the whole-mouth taste test, 5 concentrations of sweet, bitter, sour, and salty solutions were sipped and swished in the mouth twice in a counterbalanced order. A total of 40 tests were done to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Spontaneous recovery of olfactory function has been observed in one‐third of patients within two to three years of infection, but the loss of smell can remain stable in the remaining patients 17,18 . On the other hand, an upper respiratory tract infection is not one of the most common etiologies of gustatory dysfunction 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spontaneous recovery of olfactory function has been observed in one‐third of patients within two to three years of infection, but the loss of smell can remain stable in the remaining patients 17,18 . On the other hand, an upper respiratory tract infection is not one of the most common etiologies of gustatory dysfunction 19 …”
Section: Discussionmentioning
confidence: 99%
“…17,18 On the other hand, an upper respiratory tract infection is not one of the most common etiologies of gustatory dysfunction. 19 It has been reported that the frequency of olfactory dysfunction in COVID-19 patients ranges from 22% to 68%, with the frequency of gustatory dysfunction ranging from 20% to 33%. 2 The pathophysiology of olfactory and gustatory dysfunctions in COVID-19 patients remains unclear, but the damage to the olfactory neuroepithelium, or olfactory central pathways may be possible reasons surrounding olfactory dysfunction.…”
mentioning
confidence: 99%
“…In this study, the taste function was measured by both WMTT 8 and the new WETT. There was a minimum 10-minute break between taste tests.…”
Section: Taste Testsmentioning
confidence: 99%
“…In Asia, Japan was the first country to use the whole-mouth gustatory test to study the gustatory function of Japanese subjects, followed by China, South Korea, and Taiwan (3)(4)(5)(6). Hwang CS et al ( 4) tested five basic tastes, including sour, sweet, salty, umami, and bitter in 2018, and obtained the normal range for a Korean population.…”
Section: Introductionmentioning
confidence: 99%